Amniotic fluid sludge - O. A. Pustotina (Медицинский совет, 2018)
Objective: Evaluate the efficacy of combination therapy for the prevention of obstetric and perinatal complications in women with amniotic fluid (AF) ‘sludge’. Study Design: 29 women (of which 8 with the length of the cervix (LC) > 25 mm, 21 with the LC ≤ 25 mm) with AF ‘sludge’ detected by transvaginal ultrasound (TV-US) at 15-24 weeks of gestation received antibacterial therapy, additionally prescribed Indometacin and/or vaginal progesterone (VP). The women underwent the dynamic monitoring of the LC, the amount of AF ‘sludge’, the course of pregnancy, the postnatal and early neonatal period. A histological study of the secundines was conducted in women with preterm labor (PL). Results: the presence of AF ‘sludge’ is associated with the longterm infectious-inflammatory diseases during pregnancy. The outcomes of pregnancy and the probability of the development of infectious complications in the postpartum and early neonatal period were directly determined by the presence of additional risk factors and the antibiotic therapy regimen as part of the combination treatment. Thus, the antibacterial therapy in women with the LC> 25 mm was associated with congenital pregnancy and the absence of infectious complications in the postnatal and early neonatal period in 62.5% of women, whereas in women with the LC ≤ 25 mm in 52.3% of women. The most unfavorable prognosis was identified in women with threatening PL and AF ‘sludge’. The intravenous antibacterial therapy is much more efficient than oral /vaginal one as part of the combination therapy to prevent adverse pregnancy outcomes and the manifestation of intrauterine infection (IUI) in the newborns.